Comparative Analysis of Liver Enzymes and Immunological Markers in Hepatitis a Patients versus Healthy Controls in Salah Al-Din, Iraq - Karim Mahmoud, Mohammed Abbas Abdel; Hani Daoud, Fatima Al-Zahra Mohsen; Mohammed Aloun, Mohammed Khaled; Mustafa, Mohammed Ahmed (Journal of Science in Medicine and Life, 2025)
Background: Hepatitis A virus (HAV) infection is an acute viral hepatitis with significant global prevalence, particularly in regions with poor sanitation. While most cases are self-limited, HAV can cause severe liver injury in adults, mediated largely by the host immune response rather than direct cytopathic effect of the virusamboss.com. We aimed to compare liver function enzymes and immunological markers between HAV-infected patients and healthy controls to elucidate the immunopathological changes in acute HAV infection. Methods: A case-control study was conducted involving 20 patients with acute HAV (aged 20–40, anti-HAV IgM positive) and 20 age-matched healthy controls from Balad and Dujail districts, Salah al-Din, Iraq. Venous blood samples were collected for biochemical liver enzymes [alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total bilirubin] and for immunological assays. Serum cytokine levels (including interleukin-6 and interleukin-10) were measured by ELISA, and T-lymphocyte subsets (CD4^+ and CD8^+ T cells) were analyzed by flow cytometry. Descriptive statistics (mean ± SD) were calculated, and patients vs. controls were compared by independent t-tests. Results: HAV patients showed markedly elevated liver enzymes compared to controls: mean ALT was 174 ± 80 U/L vs. 25 ± 4 U/L in controls, AST 160 ± 90 vs. 27 ± 6 U/L, ALP 320 ± 150 vs. 90 ± 30 U/L, and total bilirubin 2.8 ± 2.0 vs. 0.6 ± 0.2 mg/dL (all p < 0.001). Immunologically, patients had significantly higher serum IL-6 levels (36.5 ± 12.8 vs. 5.1 ± 2.4 pg/mL, p < 0.001), indicating an acute inflammatory response. Tumor necrosis factor-alpha (TNF-α) was also elevated (25 ± 15 vs. 8 ± 4 pg/mL, p < 0.001). In contrast, the anti-inflammatory cytokine IL-10 rose only slightly (18 ± 9 vs. 15 ± 5 pg/mL) with no statistically significant difference (p = 0.17). Flow cytometry revealed a disrupted lymphocyte profile: HAV patients had a lower percentage of CD4^+ T cells (32.0 ± 7.8% vs. 43.2 ± 7.2% in controls, p < 0.001) and a higher percentage of CD8^+ T cells (40 ± 10% vs. 26 ± 5%, p < 0.001). This corresponds to an inverted CD4:CD8 ratio in patients, reflecting heightened cytotoxic T-cell activation. Conclusions: Acute HAV infection is associated with dramatic increases in liver enzymes and pro-inflammatory cytokines, alongside alterations in T-cell subsets. Elevated ALT and AST confirm significant hepatocellular injury, while heightened IL-6 and TNF-α levels indicate a strong inflammatory cytokine response. The reduction in CD4^+ T-cell proportion (with concomitant CD8^+ expansion) suggests an intense cell-mediated immune reaction during acute HAV. These immunological disturbances likely contribute to liver damageamboss.com. Clinically, our findings highlight that measuring cytokines such as IL-6 may be useful in gauging the severity of acute hepatitis A, and that profound changes in T-cell profiles (e.g. low CD4:CD8 ratio) could serve as an immunological marker of aggressive disease. Preventive vaccination and early identification of hyper-inflammatory responses are recommended to improve management of HAV, especially in adult patients at risk of severe outcomes.